(untitled) (Bioscience Journal, 2015)
This research work objective was to optimize the micropropagation of potato cultivars through the use of new light sources in the growth rooms. Treatments consisted of three potato cultivars (Asterix, Catucha and Macaca), and five light sources (blue, green and red LEDs; Growlux and white fluorescent lamps). The explants consisted of nodal segments containing one bud, isolated from plantlets grown in vitro. The experimental design was completely randomized arranged in a 3x5 factorial, with eight replications. Each experimental unity consisted of a flask with five explants. Three 28-day consecutive subcultures were carried out in MS semi-solid medium, in growth-room under controlled conditions (temperature = 25+2 ºC; photoperiod = 16 hours; light intensity = 20 Î¼mol m-2 s-1). At the end of each subculture, the bud number per plantlet, plantlet length and internode length were evaluated. After the third subculture, the concentrations of carotenoids and a- and b-chlorophylls were also determined. Different micropropagation efficiencies were found among potato cultivars grown in vitro conditions: ’Macaca’ was the most and ’Catucha’ the least responsive cultivar. The growth room light sources differently affected the potato plantlet development: red and green LEDs were the most and least recommended for plantlet development, based on the results of bud number per plantlet, plantlet length, and leaflet concentrations of a- and b-chlorophylls and carotenoids.Â